2013
DOI: 10.1097/shk.0b013e31829727f1
|View full text |Cite
|
Sign up to set email alerts
|

Post Resusicitation Fluid Boluses in Severe Sepsis or Septic Shock

Abstract: Postresuscitation FBs are common in septic patients, meet limited success, and may be harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 35 publications
4
55
2
Order By: Relevance
“…The use of post-resuscitation fluid boluses of any kind in sepsis has limited success and may be harmful. Bihari et al studied 184 fluid boluses in 50 patients with sepsis after initial resuscitation and found minimal increase in MAP and urine output following a fluid bolus in this context, yet a significant decrease in the PaO 2 /FiO 2 ratio [70].…”
Section: Recent Studies Of Gdft Within An Enhanced Recovery Programmentioning
confidence: 99%
“…The use of post-resuscitation fluid boluses of any kind in sepsis has limited success and may be harmful. Bihari et al studied 184 fluid boluses in 50 patients with sepsis after initial resuscitation and found minimal increase in MAP and urine output following a fluid bolus in this context, yet a significant decrease in the PaO 2 /FiO 2 ratio [70].…”
Section: Recent Studies Of Gdft Within An Enhanced Recovery Programmentioning
confidence: 99%
“…As the absence of calcium and high chloride levels in 4 % albumin (CSL Biotherapies; which contains the following: sodium 140 mmol/l, chloride 128 mmol/l, albumin 40 g/l and octanoate 6.4 mmol/l) may lead to clinically significant effects, we further analysed data from our recently conducted price study [1], after 149 fluid boluses with 4 % albumin administration. The amount of 4 % albumin administered was 500 (250-500) ml [median (IQR)] and acid-base status and serum electrolytes were analysed with an ABL700 series (Radiometer Medical ApS, Brønshøj, Denmark) before and 1 h after fluid administration.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated harm with standardizing liberal fluid resuscitation, notably when given beyond the initial hours of EGDT. [16][17][18][19] On the contrary, anecdotal experience and a few studies show the benefit of out-of-hospital fluid resuscitation by emergency medical services, which suggest that early fluid resuscitation might be better. 20,21 The present study is the first, to our knowledge, to examine the timing of fluid resuscitation in patients with severe sepsis and septic shock within the first 6 h in the ICU.…”
mentioning
confidence: 99%